Peran Kesejahteraann Psikologi Dalam Memediasi Pengaruh Kepemimpinan Transformasional, Budaya Kerja, Dan Beban Kerja Terhadap Kinerja Guru (Studi Kasus pada Guru SMA Negeri se- Kabupaten Pemalang) - Dwi Winanto, Muhammad Anri; Cahyaningdyah , Dwi (Business and Accounting Education Journal, 2025)
Teacher performance is a key factor in determining educational quality; however, in practice, it continues to face various organizational and psychological challenges. This study aims to analyze the effects of principals’ transformational leadership, work culture, and workload on teacher performance, with psychological well-being serving as a mediating variable. A quantitative approach with a cross-sectional survey design was employed. The research respondents were public senior high school teachers in Pemalang Regency, selected using proportional sampling techniques. Data were collected through Likert-scale questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that transformational leadership and work culture have a positive and significant effect on teacher performance, while workload has a negative and significant effect. Furthermore, psychological well-being has a positive and significant effect on teacher performance and mediates the relationships between transformational leadership, work culture, workload, and teacher performance. These findings highlight the critical role of psychological well-being as a strategic non-material resource in enhancing teacher performance. This study contributes to the development of educational management science by strengthening the integration of Resource-Based Theory and the PERMA model within the context of secondary education, and it provides practical implications for policymakers in formulating sustainable strategies to improve teacher performance.